A novel calibration method for portable X-ray fluorescence analysis of printed circuit boards - Jandric, Aleksander (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2025)
Printed circuit boards (PCBs) are the most complex and valuable component of electronic devices, but only 34% of them are recycled in an environmentally sound manner. Improving the recycling rate and efficiency requires a fast, reliable and uncostly analytical method. Although the X-ray fluorescence (XRF) shows high potential, it is often unreliable. In this study, we propose a novel XRF methodology for the elemental analysis of PCBs, using the certified reference material (CRM) to decrease uncertainty and enhance accuracy. The results show significant improvement in robustness and accuracy of portable XRF(pXRF) analyses for elements Cu, Pb, Ni, As and Au, with a relative average inaccuracy of approximately 5% compared to referenced values. The methodology validation carried out by comparing pXRF and inductively coupled plasma mass spectroscopy analyses of personal computer motherboard samples shows no statistically significant difference for elements Cu, Cr and Ag. The study shows that the calibration of pXRF by CRMs enables the necessary analysis of PCBs in an efficient and reliable manner and could be also be applied to different types of PCBs and other electronic components, batteries or contaminated soil samples